THE INSTITUTIONAL SYSTEM OF THE COMMON SECURITY AND DEFENCE POLICY (CSDP) OF THE EUROPEAN UNION: STRUCTURE AND MECHANICS - M. S. Fedorov (Vestnik MGIMO-Universiteta)
The article deals with the system of EU's functional units responsible for conducting crisis management within the framework of the Common Security and Defense Policy (CSDP). It analyses their structure and particular features. The author puts forward three main factors, which affected the shape of this system. First, it is the exclusively intergovernmental nature of the CSDP and the veto-power of EU member states in this field. Second, the EU-US and the EU-NATO relations have also influenced the shape of the CSDP organizational structures. On the one hand, the Alliance has served as an example of a successful security organization for the European integration strategists. On the other, Washington has always sought to embed the European security and defense integration into NATO and to control it. Third, the CSDP institutional system embodies a specific approach towards crisis management, elaborated by the EU - a combination of both military and civil instruments of peacemaking (the so-called "civil-military synergy"). Thus, there are two chains of units within the CSDP, designed for planning and conducting military operations and civil missions respectively. Having analyzed political and operational units of the CSDP the author concludes that, overall, the created institutional system is well-suited to the ambitions of the EU in the field of crisis management. However, the EU member states cannot use the potential of this system to the full because of the political differences that divide them.